Charles Linza McNary papers - McNary, Charles Linza, 1874-1944.
Correspondence, memoranda, speeches, notebooks, legislative files, pamphlets, clippings, printed matter, and other papers relating to McNary's career as a justice of the Oregon Supreme Court and U.S. senator from Oregon. Subjects include domestic affairs such agriculture, conservation, Indian affairs, McNary-Haugen bill, and tariffs. Other subjects include McNary's nomination as the Republican candidate for the vice-presidency in 1940; U.S. neutrality, 1939-1941; Lend-Lease legislation; and the Burke-Wadsworth compulsory military training bill. Correspondents include Ralph H. Cake, John Couzens, Herbert Hoover, Hiram Johnson, Richard L. Neuberger, Gerald P. Nye, Ben Peterson, Joseph P. Tumulty, Wallace H. White, and Wendell L. Willkie.
Justice of the Oregon Supreme Court and U.S. senator from Oregon.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room.
Keywords: Cake, Ralph H. -- 1891- -- Correspondence; Couzens, John -- Correspondence; Hoover, Herbert, -- 1874-1964 -- Correspondence; Johnson, Hiram, -- 1866-1945 -- Correspondence; Neuberger, Richard L. -- 1912-1960 -- Correspondence; Nye, Gerald P. -- 1892-1971 -- Correspondence; Peterson, Ben -- Correspondence; Tumulty, Joseph P. -- 1879-1954 -- Correspondence; White, Wallace H. -- 1877- -- Correspondence; Willkie, Wendell L. -- 1892-1944 -- Correspondence; Oregon. -- Supreme Court; Agriculture -- United States; Conservation of natural resources -- United States; Courts -- Oregon; Draft -- United States; Indians of North America -- Government relations; Law -- Oregon; Lend-lease operations (1941-1945); Neutrality -- United States; Tariff -- United States; Vice-Presidents -- United States -- Election; World War, 1939-1945 -- Economic aspects; World War, 1939-1945 -- United States; Oregon -- Politics and government; United States -- Foreign relations -- 1933-1945.; United States -- Politics and government -- 1901-1953.; Jurists; Senators, U.S. Congress -- Oregon